Lactate Dehydrogenase-A (LDH-A) Preserves Cancer Stemness and Recruitment of Tumor-Associated Macrophages to Promote Breast Cancer Progression - Wang, Shengnan; Ma, Lingyu; Wang, Ziyuan; He, Huiwen; Chen, Huilin; Duan, Zhaojun; Li, Yuyang; Si, Qin; Chuang, Tsung-Hsien; Chen, Chong; Luo, Yunping (Frontiers in Oncology, 2021)
Increasing evidence reveal that breast cancer stem cells (BCSCs) subtypes with distinct properties are regulated by their abnormal metabolic changes, however, the specific molecular mechanism and its relationship with tumor microenvironment are not clear. In this study, we explored the mechanism of lactate dehydrogenase A (LDHA), a crucial glycolytic enzyme, in maintaining cancer stemness and BCSCs plasticity, and promoting the interaction of BCSCs with tumor associated macrophages (TAMs). Firstly, the expression of LDHA in breast cancer tissues was much higher than that in adjacent tissues and correlated with the clinical progression and prognosis of breast cancer patients based on The Cancer Genome Atlas (TCGA) dataset. Moreover, the orthotopic tumor growth and pulmonary metastasis were remarkable inhibited in mice inoculated with 4T1-shLdha cells. Secondly, the properties of cancer stemness was significantly suppressed in MDA-MB-231-shLDHA or A549-shLDHA cancer cells, including the decrease of ALDH+ cells proportion, the repression of sphere formation and cellular migration, and the reduction of stemness genes (SOX2, OCT4 and NANOG) expression. However, the proportion of ALDH+ cells (epithelial-like BCSCs, E-BCSCs) was increased and the proportion of CD44+ CD24− cells (mesenchyme-like BCSCs, M-BCSCs) was decreased after LDHA silencing, suggesting a regulatory role of LDHA in E-BCSCs / M-BCSCs transformation in mouse breast cancer cells. Thirdly, the expression of epithelial marker E-cadherin, proved to interact with LDHA, was obviously increased in LDHA-silencing cancer cells. The recruitment of TAMs and the secretion of CCL2 was dramatically reduced after LDHA was knocked down in vitro and in vivo. Taken together, LDHA mediates a vicious cycle of mutual promotion between BCSCs plasticity and TAMs infiltration, which may provide an effective treatment strategy by targeting LDHA for breast cancer patients.